Floating Maximally Many Boats: A Preference for the Broad Distribution of Market Benefits - Askland, A. (Journal of business ethics, 2002)
Market economics can overreach and reduce all human activities to market-governed activities. More than a market-inspired explanation for human activities, it offers a normative account of how all goods and services should be distributed by private parties negotiating mutually agreeable terms. This paper argues that market values and practices are constrained by other fundamental values and practices. Liberal values are generally consistent with, though they are not reducible to, market values. Democratic and egalitarian values often contrast with market values. The distribution of market benefits should accommodate those democratic and egalitarian values which constitute a polity's core commitments (and those core commitments need to be reasserted regularly). Indeed, market stability depends upon a general distribution of its benefits. Incentives to productive activity entail inequalities, but the terms of those inequalities are subject to review. Internal refinements to specific markets can reduce inequalities by promoting the fairness of market operations and by increasing the number of effective participants.